PENGARUH KOMPENSASI TERHADAP DISIPLIN KARYAWAN DI PT.PUTERA PAPAN HUTAMA - sasangka, indra; Suwarna, Asep; Juliansyah, Rana (2018)
Implementation of the activity or activities in an organization is busy cally intended to achieve the goals or objectives that have been shet he previously. Employee performance is the work of employees in performing their duties in accordance with the responsibilities assigned to all employees. Compentation is believed to affect the performace of the employess discipline and PT Putera Papan Hutama. The method used is descriptive method verivikatif case study approach, using data collected with a list of question prepared by the scale option five to 37 employees PT Putera Papan Hutama as the respondent. Data processing technique used is to use the correlation coefificient analisis, Sample linear regression coefficients and determinants. By using the SPSS software program to find The effect compentation amounting the value of employees disciplined PT Putera Papan Hutama by 65,4 % and 34,6 % is influenced by other variables that are not in meticulous.